Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community. (1st May 2023) - Yin, Yanan; Li, Mengtong; Tao, Xiaohui; Yang, Chao; Zhang, Wenrong; Li, Haichao; Zheng, Yucong; Wang, Xiaochang; Chen, Rong
Abstract: Fungal degradation of cellulose is a key step in the conversion of organic matter in composting. This study investigated the effects of adding 10% biochar (including, prepared from corn stalk and rape stalk corresponding to CSB and RSB) on organic matter transformation in composting and determined the role of cellulase and fungal communities in the conversion of organic matter. The results showed that biochar could enhance the conversion of organic matter, especially in RSB treatment. Biochar could increase cellulase activity, and RSB could enhance 33.78% and 30.70% the average activity of cellulase compared with the control and CSB treatments in the mesophilic to thermophilic phase, respectively. The results of high throughput sequencing demonstrated that Basidiomycota dominant in mesophilic phase, and Ascomycota dominant in other phases of composting. The redundancy analysis showed that Alternaria, Thermomycees, Aspergillus, Wallemia, and Melanocarpus might be the key fungi for the degradation of organic matter, and Fusarium, Penicillium, and Scopulariopsis may promote the conversion of organic matter. Network showed that the addition of RSB changed the interactions between fungal communities and organic matter transformation, and RSB treatment enriched members of Ascomycota related to organic matter transformation and cellulase activity. These results indicated that RSB improved organic matter conversion by enhancing the role of cellulase and fungal communities. Highlights: Adding 10% rape stalk biochar in composting increased cellulase activity. Adding 10% rape stalk biochar in composting enriched Ascomycota community. Adding 10% rape stalk biochar induced cellulase secretion from Enyloma. Rape stalk biochar enhanced organic matter transformation and compost maturity.